Study of atmospheric air pollution in Sub-Saharan Africa : Case of Cotonou (Benin) : Physicochemical characterization of urban particulate matter and toxicological effects on human bronchial epithelial cells (BEAS-2B) cultured in vitro - (:unkn) unknown (My University, 2013)
Air pollution and its adverse health effects have shown a growing interest in developing countries. This study deals with this subject and is one of the first conducted in African countries, particularly in Benin. Our results showed that the quality of gasoline used in cotonou was poor, characterized by the absence of additive and a high concentration of benzene. Thus, it could be responsible for the degradation of the city air quality. Therefore, particulate matter samples (PM₂․₅ and PM>₂․₅) were collected in St Michel neighborhood at Cotonou and results showed very high levels of particles in the ambient air. Physicochemical characterization of these particles revealed a presence of various chemicals compounds (ions, metals, VOCs, paraffins, PAHs, ect.) in higher proportion in PM₂․₅ than PM>₂․₅. The respiratory system, the main way of exposure to these airborne particles, was investigated through an in vitro study assessing the toxic potential of PM on human bronchial epithelial cells (BEAS-2B). It has been demonstrated that the two types of particules have cytotoxic properties and ability to induce gene expression of organic compounds metabolizing enzymes and to generate oxidative stress. These particles have triggered the inflammatory process through the induction of gene expression and protein secretion of cytokines, and changes in the arachidonic acid pathway (leukotrienes, prostaglandin, and thromboxane). Finally, comparative approach for PM₂․₅ sampled in three West African cities highlighted the closeness of particles characteristics in Benin, Côte d'Ivoire and Senegal, and a significant contribution of road traffic emissions in the air pollution.
Keywords: African Research